2002
DOI: 10.1081/pdt-120002232
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Erosion and Swelling on the Dissolution of Theophylline from Low and High Viscosity Sodium Alginate Matrices

Abstract: The extent of dissolution of theophylline from sodium alginate matrices has been studied in water and HCl. Surprisingly, it was observed that the dissolution rate was very fast for the low viscosity (LV) material in water and for the high viscosity (HV) in acid, whereas slow release was seen for LV in acid with very slow release for the HV in water. The extent of erosion and swelling of the matrices (with and without drug and with and without stirring) was determined from simple weighing experiments. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 14 publications
2
25
0
2
Order By: Relevance
“…However, the use of a gradient-pH system may have also provided good prediction of in vivo results. The release of PB was dependant on temperature and pH, which is in line with previous studies using SA-drug formulations (34,35). As shown in Fig.…”
Section: Drug Release Studies and In Vitro Dissolutionsupporting
confidence: 77%
“…However, the use of a gradient-pH system may have also provided good prediction of in vivo results. The release of PB was dependant on temperature and pH, which is in line with previous studies using SA-drug formulations (34,35). As shown in Fig.…”
Section: Drug Release Studies and In Vitro Dissolutionsupporting
confidence: 77%
“…The lower rehydration of beads that were prepared at shorter curing time may be correlated to the incomplete cross-linking of the sodium alginate. 9,14,15 When MZ-loaded Ca-alginate beads were evaluated for drug release in 0.1 N HCl, pH 1.2 (Figure 7), 70% to 90% release of drug from the beads occurred within 20 to 30 minutes, which was in accordance with Murata et al, 13 Multiple regression data revealed retarding effect of curing time on drug release, which might be caused by slower penetration of medium in highly cross-linked beads, but the overall drug release was governed by solubility of drug in dissolution medium and not by swelling properties of beads.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, during ionotropic gelation, curing time can be a crucial factor in governing the entrapment efficiency. [1][2][3][4][5][6][7][11][12][13][14] Metronidazole (MZ) was selected as a model drug for incorporation in calcium alginate beads. With drug concentration and curing time as variables, 3 2 factorial design was applied.…”
Section: +mentioning
confidence: 99%
“…The controlled-release of drug substances from sodium alginate matrices would be expected to correlate with the swelling and erosion of the polymer (8,9). The alginate concentrations in the gel and diffusion layers around the polymer matrix could be expected to range from very high values at the boundary with the unhydrated alginate to relatively dilute concentrations at the boundary with the bulk alginate solution.…”
Section: Concentration Effect On Viscoelasticitymentioning
confidence: 99%
“…Current pharmacopeial specifications (USP-NF) for sodium alginate do not enable the characterization of variations in the molecular weight distribution and/or chemical composition of sodium alginate. Since these variations can markedly affect the processability or performance of a sodium alginate-containing pharmaceutical product (8,9), adherence to the USP-NF monograph may not ensure the interchangeability of sodium alginates from different sources or even various batches from the same manufacturer. Previous studies have shown that the inter-manufacturer and/or inter-batch (lot) variability of excipients can exert a significant effect on the performance of the final formulations, even though these excipients meet the pharmacopeial specifications (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%